The Validation Path of Hypoxia PET Imaging: Focus on Brain Tumours - Quartuccio, Natale; Asselin, Marie-Claude (Current Medicinal Chemistry, 2018)
Background: Gliomas are brain tumours arising from the glia, the supportive tissue of the central nervous system (CNS), and constitute the commonest primary malignant brain tumours. Gliomas are graded from grade I to IV according to their appearance under the microscope. One of the most significant adverse features of high-grade gliomas is hypoxia, a biological phenomenon that develops when the oxygen concentration becomes insufficient to guarantee the normal tissue functions. Since tumour hypoxia influences negatively patient outcome and targeting hypoxia has potential therapeutic implications, there is currently great interest in imaging techniques measuring hypoxia. Objectives: The aim of this review is to provide up to date evidence on the radiotracers available for measuring hypoxia in brain tumours by means of positron emission tomography (PET), the most extensively investigated imaging approach to quantify hypoxia. Methods: The review is based on preclinical and clinical papers and describes the validation status of the different available radiotracers. Results: To date, [F-18] fluoromisonidazole ([18F]FMISO) remains the most widely used radiotracer for imaging hypoxia in patients with brain tumours, but experience with other radiotracers has expanded in the last two decades. Validation of hypoxia radiotracers is still on-going and essential before these radiopharmaceuticals can become widely used in the clinical setting. Conclusion: Availability of a non-invasive imaging method capable of reliably measuring and mapping different levels of oxygen in brain tumours would provide the critical means of selecting patients that may benefit from tailored treatment strategies targeting hypoxia.
Keywords: Hypoxia